PERILAKU MANAJEMEN KEUANGAN PEDAGANG PEREMPUAN DI PASAR KALISAT KABUPATEN JEMBER - Safira, Serli Vebriana; Supeni, Retno Endah; Sari, Maheni Ika (Relawan Jurnal Indonesia, 2023)
The phenomenon that occurs to female traders in the Kalisat market is financial knowledge where traders in the Kalisat market do not understand how to manage finances properly even though the proceeds from their sales are set aside to be saved every day. The researcher intends to measure the financial management behavior of female traders in the Kalisat market, Jember district by raising variables regarding financial management which refer to financial knowledge, income, financial attitude, personality and financial management behavior. The data obtained by distributing questionnaires through the Google Form. The population measurement was conducted by interviewing the head of the market management and the results obtained were 1,520 female traders. The sampling technique used the Slovin formula and the results obtained were 320 respondents with the criteria of being female, aged over 17 years and trading for more than 5 years. The method is a quantitative approach with multiple linear regression tests. The results of the study stated that the financial management behavior of female traders in the Kalisat market in Jember district was positively and significantly influenced by the variables of financial knowledge, income, financial attitudes, and personality.